Vector Competence of Argentine Mosquitoes (Diptera: Culicidae) for West Nile virus (Flaviviridae: Flavivirus) - Micieli, María Victoria (2013)
We examined the ability of Culex pipiens L. complex mosquitoes from Argentina to vector West Nile virus (WNV) to assess their role in the transmission of WNV in South America. Several egg rafts of Culex spp. were collected from different breeding sites in the suburbs of the city of La Plata, Argentina, and a subset of each progeny was scored with morphological and genetic species indicators. Surprisingly, we did not find Cx. pipiens form pipiens, but found evidence of genetic hybrids of Culex quinquefasciatus and Cx. pipiens f. molestus. We then used morphological traits to create two colonies predominantly composed of one of these two taxa, although some hybrids are likely to have been included in both. These colonies were used in vector competence studies using NY99 and WN02 genotype strains of WNV obtained in New York State. As controls, we also tested colonies of U.S. Cx. quinquefasciatus and Cx. pipiens f. molestus. Additional Culex larvae from three drainage ditches near the cities of La Plata and Berisso, Argentina, were identified by morphological and high-resolution molecular markers (microsatellites) as Cx. quinquefasciatus Say, Cx. pipiens form molestus, and hybrids. Results indicate that Argentinian Culex are competent but only moderately efficient vectors of WNV and are less susceptible to this virus than comparable U.S. mosquito strains. Studies of vertical transmission of NY99 virus by Cx. pipiens f. molestus hybrids from Argentina yielded a minimal filial infection rate of 1.19 from females feeding during their second and later bloodmeals.